Glycemic index and glycemic load in cardiovascular disease risk - Yadav, Dhananjay; Mishra, Meerambika; Jadaun, Pratiksha; Choi, Eunhee; Priyadharsini, R.; Kong, In Deok (Progress in Nutrition, 2016)
Diet comprises of many nutritious components like carbohydrates, protein, fats and fibers. Each component has different functions which directly or indirectly involved in the growth and maintenance of the body. The behavioral modification of eating habits using high glycemic and glycemic load diet leads to certain changes in physiologic and biologic changes in an individual. This study discusses and summarizes the recent literature on high glycemic index/glycemic load carbohydrate diet and its pathological relationship in causing cardiovascular disease and its risk factors. High carbohydrate intake has an adverse effect on glucose and lipid metabolism, as a result of which may increase the risk of cardiovascular disease (CVD). A number of cohort studies examined the role of glycemic index and glycemic load on cardiovascular events. Randomized control trials and intervention studies support the hypothesis that high glycemic index and glycemic load diet could increase the risk of CVD in individuals with different outcomes in men and women. The inclusion of glycemic index and glycemic load in dietary recommendations may help in reducing the prevalence and incidence of cardiovascular disease and its risk factors.